[18F]FDG PET/CT Mapping of Metastatic Spread in Left Testicular Carcinoma: A Rare Visualization of Lymphatic Pathway - Saju, Austin; Sonavane, Sunita; Menon, Santosh; Basu, Sandip (World Journal of Nuclear Medicine, 2025)
We report a rare case of metabolic visualization of the entire left testicular lymphatic drainage pathway by [18F]FDG-PET/CT (18F-fluorodeoxyglucose positron emission tomography/computed tomography) in a 22-year-old male with biopsy-proven non-seminomatous germ cell tumor (NSGCT) of the left testis, presenting with extensive metastases to the retroperitoneal lymph nodes (RPLNs), liver, lungs, and skeleton. Primary staging with [18F]FDG-PET/CT demonstrated intense radiotracer uptake in both the primary tumor and multiple metastatic sites. Notably, a rare linear pattern of [18F]FDG avidity was observed along the left testicular lymphatic drainage pathway, following the course of the left testicular vein. While the anatomical pathway of lymphatic dissemination in testicular malignancies is well-characterized and [18F]FDG avidity in RPLNs has been previously reported, direct metabolic visualization of the entire lymphatic drainage pathway on [18F]FDG-PET/CT has not been documented. This case further underscores the utility of [18F]FDG-PET/CT in the initial staging of advanced NSGCT, particularly in detecting skeletal metastases that may be subtle or occult on conventional imaging, bearing important clinical and prognostic implications.
Keywords: testicular cancer; [18F]FDG-PET/CT; metastasis; embryonal carcinoma